Enseñanza de las ciencias en aulas inclusivas - Hernández Ballesteros, María Andrea; Malagon, Rusby; Bautista, Germán (Revista Científica, 2011)
This research was performed in order to contribute to the teaching-learning processes of students with cognitive deficits (DC) included in the regulars classrooms. This proposal stem from the problems that became evident from the teaching practice. The inclusion of these populations to the regular classroom turns out to be a task that presents many challenges to the teacher given the special cognitive conditions these students have. The usual strategies followed in order to guide the students to access scientific knowledge that requires high level of abstraction are not adequated. This research aims to design and implement a classroom strategy that encourages development of thinking skills by the study of the manifestations of energy in several physical processes. This strategy is aimed to find some characterization of some obstacles in cognitive processes of physics learningas well. Likewise to identify some of the teaching activities of most relevance to science teaching.